An Efficient Method for Generating Optimal OBDD of Boolean Functions - Singh, Ashutosh; Mohan, Anand (Canadian Center of Science and Education, 2008)
An efficient method of finding optimal (OBDD) of an n variable Boolean function is presented that offers a simple and straightforward procedure for optimal OBDD generation along with storage economy. This is achieved by generating n! fold tables and applying node reduction rules to each fold table directly instead of generating all n! OBDDs of the function.